(untitled) (Revista cientifica In Vestigium Ire, 2020)
The study refers to an applied research in the municipality of Silvania, whose objective was to determine the social, economic and cultural characteristics that define the enterprising woman in the municipality of Silvania, department of Cundinamarca; from a random sample of 50 women, who, at the date of the study, had a business, some formalized and others without managing their Unique Tax Registration -RUT-. The basic instrument used was an interview accompanied by a survey designed for microentrepreneurs in the urban area of the municipality, generating a descriptive approach and at the same time, with an exploratory approach, since no studies were made on the subject. Among the results found, it is reflected the lack of knowledge that women microentrepreneurs have in relation to government programs to support entrepreneurship and on the other hand, the importance and motivation to obtain training to strengthen sustainable strategies for their businesses.